Metaphors of Textual Materiality in Late Medieval Middle English Sermons. - Baker, Eleanor (Studies in Philology)
This article explores the use of book metaphors in a selection of late medieval Middle English sermons, both orthodox and Wycliffite. These book metaphors engage with the materiality of the codex in a variety of ways, drawing on understandings of scribal practice, the dyptical structure of the physical book, learning and reading practices, and parchment production. Although sermon texts are usually considered void of any creativity, these book metaphors prove diverse and inventive. Through a close reading of particular case studies, I argue that sermons often express an ambivalence toward the material text, at once warning of the biblioclastic effect of sin and the textual manipulation of the devil and offering the devout a metaphorical means of writing their own salvation. The article engages with historical criticism on the use, purpose, and function of the sermon form while considering how these written and spoken texts themselves responded to late medieval literacy, book use, book production, and other material objects.